Social and political correlates of adult and dependent-child COVID-19 vaccination behavior in rural America - J. Tom Mueller; Ann Tickamyer; Brian C. Thiede; Kai Schafft; Alan Graefe (Preventive Medicine Reports, 2024)
Objective: This paper describes the individual-level correlates of self and dependent-child COVID-19 vaccination behavior among adults in rural America. Methods: We draw on the data from a large-scale survey of rural Americans conducted in 2022, after most Americans had the opportunity to receive the vaccination easily and freely. The survey yielded an analytic sample of 841 adults and 530 adults with dependent children. We fit a series of linear probability models predicting vaccine refusal and full vaccination for adult respondents and vaccine refusal and full vaccine coverage among their dependent children. Predictors of interest include political party, social and economic conservatism, race and ethnicity, age, education, and workplace vaccine requirements. Results: We find political party, ideology, education, and work requirements were significant (p <.05) drivers of rural adults’ vaccination behavior, and that the correlates of vaccine refusal and full vaccination largely mirrored one another among adults. For dependent children, few of our focal predictors are associated with vaccination. Politics played a lesser role in children’s vaccination than for adults, and older parents were the least likely to refuse vaccines for their children. Race and ethnicity had inconsistent associations across outcomes and model specifications. Conclusion: This analysis presents important evidence on the drivers of COVID-19 vaccine behaviors among rural American households. Documentation of vaccination behaviors in settings when vaccines are widely available can isolate demand- from supply-side factors and thus inform future public health crises.